Diversité floristique des suberaies du Parc National de Tlemcen (Algerie - Letreuch-Belarouci, A. (Acta botánica malacitana, 2009)
The analysis of the ﬂoristic diversity of forest massif “Haﬁr-Zariffet” in the Tlemcen National Park has revealed the existence of 211 taxa which belong to 65 families and 164 genera. The number of taxa endemic and/or rare includes: 1 endemic algerian, 7 algero-moroccan, 11 ibero-algero-moroccan, 7 are endemic in North Africa and 11 are endemic in Iberian Peninsula and North Africa. The number of rare taxa is 26, 9 are at the same time threatened. Urgent efforts are required to preserve the cork oak as well as endemic species conﬁned to it.
Keywords: Algeria; Cork Oak Forest; diversity; Inventory; national park of tlemcen